MODEL SISTEM DINAMIK TANGKI AIR MENGGUNAKAN IDENTIFIKASI SISTEM NONLINEAR HAMMERSTEIN-WIENER - Arjoni Amir (BATAN, 2013)
A DYNAMIC SYSTEM MODEL FOR A WATER TANK USING NONLINEAR HAMMERSTEIN-WIENER SYSTEM !DENTIFICA TlON. It has been simulated experiment at a model two water tanks connected in serial using nonlinear Hammerstein Wiener system identification technique. The dynamic system to be evaluatedis taken from the voltage change of water pump as input parameter and the second tank water level as output parameter. Relationship of these parameters are SISO (Single Input,single Output) and nonlinear. Dynamic system between these parameters is expressed in a record of couple of data input-output. Combination of input parameter nonlinear block, linear block, output parameter nonlinear block, delay time nk, and application of both estimator nonlinearity piecewiece linear and sigmoidnetwork with certain nonlinear number of block will yield some nonlinear Hammerstein Wiener model structure accurately. The result of the simulation experiment yield nonlinear Hammerstein Wiener model structure is indicated by value of Loss Function (small) 0.00026746, criterion of Final Prediction Error 0.0002859, assess Best Fit 89.49 , Fit 90.32 , orde of model structure [nb = 1, ru= 6, nk = 1J, and a sum of nonlinear block (input nonlinearity and output nonlinearity), 10. MODEL SISTEM DINAMIK TANGKI AIR MENGGUNAKAN IDENTIFIKASI SISTEM NONLINEAR HAMMERSTEIN-WIENER. Telah dilakukan percobaan simulasi pemodelan sistem dinamik dua tangki air yang dihubungkan secara seri menggunakan tehnik identifikasi sistem nonlinear Hammerstein-Wiener. Sistem dinamik yang terjadi ditinjau dari perubahan tegangan listrik dari pompa air sebagai parameter input dan level air dalam tangki kedua sebagai parameter output. Hubungan kedua parameter ini adalah SISO (Single Input Single Output) dan nonlinear. Sistem dinamika antara kedua parameter ini dinyatakan dalam rekaman pasangan data input-output. Kombinasi parameter input blok nonlinear, blok linear, parameter output blok nonlinear, waktu delay nk, dan pemakaian estimator nonlinearity seperti piecewiece linear serta sigmoid network dengan jumlah blok nonlinearity tertentu akan menghasilkan beberapa struktur model nonlinear Hammerstein-Wiener yang akurat. Dari hasil percobaan simulasi diperoleh struktur model nonlinear Hammerstein-Wiener yang diindikasikan dengan nilai Loss Function (LF) yang kecil yaitu 0.00026746, kriteria Final Prediction Error yaitu 0.0002859 dan nilai Best Fit yaitu 89.49 , Fit 90.32 , orde struktur model [nb = 1, n, = 6, nk = 1J, dan dengan masing-masing jumlah blok nonlinear (input nonlinearity dan output nonlinearity) adalah 10.